2017
DOI: 10.1016/j.radcr.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic nonanastomotic axilloprofundal PTFE-bypass rupture: a case report

Abstract: A 76-year-old male patient was admitted to our emergency department with painful swelling of the right lateral chest after a fall. Imaging revealed a hematoma, secondary to rupture of a synthetic axilloprofundal bypass. In an emergency surgical procedure, the spelled hematoma was evacuated and the graft legs were successfully ligated. The patient was discharged after an uneventful hospital stay. Traumatic bypass rupture because of blunt trauma is an exceedingly rare event; however, it must be taken into consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The incidence of graft ruptures is around 5% [11]. There are limited number of studies reporting axillo-femoral graft ruptures and distortions [9][10][11][12][13][14][15]. PTFE graft rupture and development of pseudoaneurysm are rare complications in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of graft ruptures is around 5% [11]. There are limited number of studies reporting axillo-femoral graft ruptures and distortions [9][10][11][12][13][14][15]. PTFE graft rupture and development of pseudoaneurysm are rare complications in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, complete graft rupture and distortion were observed after the exact same movement. Barht et al [10] reported successfully operating a traumatic graft rupture after axillo profundal bypass in a 76-year-old patient. The incidence of graft ruptures is around 5% [11].…”
Section: Discussionmentioning
confidence: 99%